2008
DOI: 10.1302/0301-620x.90b12.21064
|View full text |Cite
|
Sign up to set email alerts
|

Midterm survival of a contemporary modular total knee replacement

Abstract: This retrospective study evaluated the midterm clinical and radiographic outcomes of a second-generation total knee replacement system. In a multicentre consecutive series of 1512 patients, 1970 knees were treated with the PFC Sigma knee system (Depuy, Warsaw, Indiana). The patients were reviewed for functional outcome, and underwent independent radiographic evaluation at a mean follow-up of 7.3 years (5 to 10). A total of 40 knees (2%) required revision, 17 (0.9%) for infection. The incidence of osteolysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 27 publications
2
34
0
2
Order By: Relevance
“…No adverse events or complications related to the new material were seen. The observed rates of radiologic loosening and wear were similar to those in other studies of primary TKAs that had a similar length of followup [4,8,15,18]. Furthermore, we noted a slightly better patellar score in the nonresurfaced patella group; this difference just approached but did not achieve statistical significance.…”
Section: Discussionsupporting
confidence: 88%
“…No adverse events or complications related to the new material were seen. The observed rates of radiologic loosening and wear were similar to those in other studies of primary TKAs that had a similar length of followup [4,8,15,18]. Furthermore, we noted a slightly better patellar score in the nonresurfaced patella group; this difference just approached but did not achieve statistical significance.…”
Section: Discussionsupporting
confidence: 88%
“…Kim et al [27] reported that the survivorship of fixed-bearing TKA was 97.1 % at 12.6 years in patients with an average age of 58.6 years and that of mobilebearing TKA was 97.1 % at 14.1 years in patients with an average age of 55.7 years. Our survival rates are similar to the reported survival rates for TKA in younger patients [12,[24][25][26][27]. Baker et al [14] reported the survival rates of 80.7 % for the cemented press-fit condylar knee (PFC; DePuy, Warsaw, IN, USA) and 75.3 % for the cementless PFC knee (DePuy) at 15 years.…”
Section: Discussionsupporting
confidence: 85%
“…Dixon et al [25] reported a 92.6 % survival rate at 15 years in patients with an average age of 67 years, using revision as an end point. Dalury et al [26] found a slight agerelated difference. They reported that the ten-year survival rate was 97.5 % for patients <55 years and 98.1 % for older patients; they concluded that survival rate was slightly lower in the younger group.…”
Section: Discussionmentioning
confidence: 93%
“…Dixon et al [14] reported a 92.6% survival rate at 15 years in patients with an average age of 67 years, using revision as an end point. Dalury et al [12] found a slight age-related difference. They reported that the 10-year survival rate was 97.5% for patients younger than 55 years and 98.1% for older patients.…”
Section: Discussionmentioning
confidence: 93%
“…Although TKAs using fixed-bearing prostheses have produced long-term survival rates of 90% or greater at 15 years [12,25,27], numerous authors have reported long-term polyethylene wear and osteolysis [3,4,21,26,28,31,34]. A mobile-bearing prosthesis was introduced to reduce polyethylene wear and osteolysis [5,20].…”
Section: Introductionmentioning
confidence: 99%